2005
DOI: 10.1177/1541204005276263
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Legal and Extralegal Factors on Statutory Exclusion of Juvenile Offenders

Abstract: The study describes implementation of legislation that excludes youth offenders from juvenile court jurisdiction and examines two elements of deterrence theory that underscored the legislation’s rationale. Between-court analyses comparing youths decertified to juvenile court with those remaining in criminal court report no between-court differences concerning the certainty of punishment. Although the criminal court was more likely to impose more severe sentences, controls on legal sentencing factors explained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
1
25
1
Order By: Relevance
“…Some research, though, does suggest no difference in punishment certainty between the two groups (Jordan and Myers 2011). Furthermore, studies suggest that convicted transferred offenders are more likely to be incarcerated (Myers 2001, Kupchik 2006) and sentenced to fairly longer periods of confinement (Fagan 1995, Myers 2003a, Lemmon et al 2005, Jordan and Myers 2011) as compared to youth processed in juvenile court, which represents strong punishment severity. From these studies, then, it appears that juvenile transfer does not meet all of the components necessary to achieve deterrence.…”
Section: Theoretical Foundationmentioning
confidence: 93%
“…Some research, though, does suggest no difference in punishment certainty between the two groups (Jordan and Myers 2011). Furthermore, studies suggest that convicted transferred offenders are more likely to be incarcerated (Myers 2001, Kupchik 2006) and sentenced to fairly longer periods of confinement (Fagan 1995, Myers 2003a, Lemmon et al 2005, Jordan and Myers 2011) as compared to youth processed in juvenile court, which represents strong punishment severity. From these studies, then, it appears that juvenile transfer does not meet all of the components necessary to achieve deterrence.…”
Section: Theoretical Foundationmentioning
confidence: 93%
“…Another explanation is that the offenders in our sample received similar rehabilitative services and punishment in the juvenile and adult systems. Indeed, scholars have found mixed evidence on the relative severity of punishment in the juvenile and adult systems (Fagan 1996;Kurlychek and Johnson 2004;Lemmon et al 2005), which leads some to conclude that these two systems differ more in their procedural elements than in their substantive effects (Feld 1999). It is particularly plausible that the subjects in our sample-older adolescents who commit less serious crimes-receive similar treatment in the juvenile and adult systems.…”
Section: Discussionmentioning
confidence: 99%
“…We elaborate on the potential explanations for this phenomenon below. When considered in conjunction with the prior research (e.g., Jordan & Myers, 2011;Kurlychek & Johnson, 2004Lemmon et al, 2005;Myers, 2003), this finding provides some evidence that transfer status may act as a cognitive heuristic, conveying information about the blameworthiness or dangerousness of the delinquent and informing court actors that harsher sanctions are warranted.…”
Section: Discussionmentioning
confidence: 58%
“…Similarly, Myers (2003) observed that transferred youth are treated more harshly than retained youth; however, he noted that transfers tended not to serve their full sentences. More recently, Lemmon, Austin, Verrecchia, and Fetzer (2005) and Jordan and Myers (2011) both found that the criminal court tends to impose more severe punishments than the juvenile court for similar offenders. Instead of reporting a leniency gap, these latter studies provide support for the notion that the transfer mechanism embodies the get tough philosophy of punishment and that transfer status signifies that especially punitive sanctions are warranted.…”
Section: Prior Research On Sentencing Transferred Juvenilesmentioning
confidence: 99%